Divergent Regulation of the Evolutionarily Closely Related Promoters of the Saccharomyces cerevisiae STA2 and MUC1 Genes - Gagiano, Marco (American Society for Microbiology, 1999)
The 5′ upstream regions of the Saccharomyces cerevisiae glucoamylase-encoding genes STA1 to -3 and of the MUC1 (or FLO11) gene, which is critical for pseudohyphal development, invasive growth, and flocculation, are almost identical, and the genes are coregulated to a large extent. Besides representing the largest yeast promoters identified to date, these regions are of particular interest from both a functional and an evolutionary point of view. Transcription of the genes indeed seems to be dependent on numerous transcription factors which integrate the information of a complex network of signaling pathways, while the very limited sequence differences between them should allow the study of promoter evolution on a molecular level. To investigate the transcriptional regulation, we compared the transcription levels conferred by the STA2 and MUC1 promoters under various growth conditions. Our data show that transcription of both genes responded similarly to most environmental signals but also indicated significant divergence in some aspects. We identified distinct areas within the promoters that show specific responses to the activating effect of Flo8p, Msn1p (or Mss10p, Fup1p, or Phd2p), and Mss11p as well as to carbon catabolite repression. We also identified the STA10 repressive effect as the absence of Flo8p, a transcriptional activator of flocculation genes in S. cerevisiae.